2018
DOI: 10.1002/adsc.201800132
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Process for (−)‐Ambrox Production Using Squalene Hopene Cyclase

Abstract: Alicyclobacillus acidocaldarius Squalene Hopene Cyclase was evolved to a biocatalyst suitable for (À)-Ambrox production at industrial scale. One round of random mutagenesis led to the identification of three variants with (E,E)-homofarnesol conversion properties improved about 1.5-to 10-fold over that of the wild type enzyme. Eight distinct amino acid mutations were identified overall; only one mutation was at the active site of the enzyme. Each of the three variants contained only two or three mutations over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 38 publications
0
76
0
14
Order By: Relevance
“…Another innovative approach to Ambrofix (296)involves a" sesquiterpene-plus-C 1 "a pproach utilizing squalenehopene-cyclase (SHC). [265,266] Ther equired substrate (E,E)homofarnesol (EEH, 303)i ss ynthesized by selective cyclopropanation of (E)-b-farnesene (301)t o302, [267] followed by (E)-selective cyclopropyl-carbinyl rearrangement of the resulting vinyl cyclopropane. [268] (E)-b-Farnesene (301)i si n turn manufactured from sugar by engineered yeast fermentation.…”
Section: Ambery Notesmentioning
confidence: 99%
“…Another innovative approach to Ambrofix (296)involves a" sesquiterpene-plus-C 1 "a pproach utilizing squalenehopene-cyclase (SHC). [265,266] Ther equired substrate (E,E)homofarnesol (EEH, 303)i ss ynthesized by selective cyclopropanation of (E)-b-farnesene (301)t o302, [267] followed by (E)-selective cyclopropyl-carbinyl rearrangement of the resulting vinyl cyclopropane. [268] (E)-b-Farnesene (301)i si n turn manufactured from sugar by engineered yeast fermentation.…”
Section: Ambery Notesmentioning
confidence: 99%
“…This result indicated that to further improve the scale of the catalytic conversion system was feasible and expecting for producing more hopene with high purity. SHC can also be used to produce other terpenoids, such as epoxydammarane (Ideno et al, 2018) and ambrox (Eichhorn et al, 2018;List and Sun, 2018). These valuable terpenoids can also be produced at a scale-up level by using the soluble OUC-SaSHC found in this study.…”
Section: Shc Has the Potential For Large-scale Production Of Hopenementioning
confidence: 93%
“…Im Zentrum dieser neuen Herstellungsmethode steht eine Squalen-Hopen-Cyclase katalysierte Polyencyclisierung. [265,266] Das bençtigte Substrat (E,E)-Homofarnesol (EEH, 303)wird durch selektive Cyclopropanierung von (E)b-Farnesen (301)zu302 [267] hergestellt, gefolgt von einer (E)selektiven Cyclopropyl-Carbinyl-Umlagerung. [268] (E)-b-Farnesen (301)wird durch einen Hefe-Fermentationsprozess aus Zucker hergestellt.…”
Section: Aufsätzeunclassified